Comparative Efficacy of Syntometrine Versus Oxytocin in Active Management of Third Stage of Labour - Sadia Wazir, Amna Fareed, Saadia Shamsher, Sadia Hanif, Anaheeta Israr, Nighat Afridi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The study’s objective is to examine the effectiveness of syntometrine and oxytocin in actively managing the third stage of labour in order to lower the risk of PPH and other undesirable third stage outcomes. Study Design: Randomized/Prospective study Place and Duration: Gynae & Obs department of Combined Military Hospital Peshawar for the duration from 1st June 2021 to 30th November 2021. Methods: This study comprised of 140 females of third stage labour. Age of the females was 18-40 years. After getting informed written consent detailed demographics of enrolled cases were recorded. Patients were equally divided in two groups. Group I had 70 patients and received syntometrine (5 IU Synthetic Oxytocin and 0.5 mg ergometrine maleate) and in group II oxytocin was given to 70 females. Outcomes among both groups were recorded in terms of blood loss and postpartum hemorrhage. SPSS 23.0 was used to analyze all data. Results: The mean age of the patients was 28.3±6.18 years and had mean BMI 27.6±11.25 kg/m2. Mean gestational age was 36.11±5.19 weeks. Frequency of primigravida was 80 (57.1%). Frequency of emergency delivery was found in 85 (60.7%) cases while 55 (39.3%) females admitted to OPD. 72 (51.4%) females were from rural areas and 67 (47.8%) cases were educated. We found that mean blood loss in group II was higher 165.1±8.66 ml as compared to group I 118.7±9.39 ml with p value <0.005. There was no any PPH found in group I while in group II PPH found in 3 (4.3%) cases. Frequency of hypertension was higher in group I. We found higher number of adverse outcomes among females of syntometrine group as compared to oxytocin group. Conclusion: In this study we concluded that use of syntometrine in third stage of labour was effective and useful in terms of reduction in blood loss and PPH as compared to oxytocin while frequency of adverse events and hypertension was higher in syntometrine group as compared to oxytocin. Keywords: Pregnant Females, Third Stage Labour, Syntometrine, Oxytocin, Blood Loss